Completion Rate and Safety of Programmatic Screening and Treatment for Latent Tuberculosis Infection in Elderly Patients With Poorly Controlled Diabetic Mellitus: A Prospective Multicenter Study. (3rd March 2021) - Huang, Hung-Ling; Huang, Wei-Chang; Lin, Kun-Der; Liu, Shin-Shin; Lee, Meng-Rui; Cheng, Meng-Hsuan; Chin, Chun-Shih; Lu, Po-Liang; Sheu, Chau-Chyun; Wang, Jann-Yuan; Lee, I-Te; Chong, Inn-Wen
Abstract: Background: Poor control of diabetes mellitus (DM) increases active tuberculosis (TB) risk. Understanding risk factors for latent TB infection (LTBI) in this population and intervention completion rates is crucial for policy making. Methods: Under a collaborative multidisciplinary team consisting of public health professionals, endocrinologists, and pulmonologists, patients aged >45 years with poorly controlled DM (pDM), defined as having a glycated hemoglobin level of ≥9% within the preceding year, were enrolled by endocrinologists from 2 hospitals; these patients underwent LTBI screening by using QuantiFERON (QFT). Once-weekly isoniazid and rifapentine for 12 weeks (3HP) or daily isoniazid for 9 months (9H) was administered by pulmonologists. QFT-positivity predictors were evaluated using logistic regression. Completion rates and safety were also investigated. Results: Among 980 patients with pDM (age: 64.2 ± 9.7 years), 261 (26.6%) were QFT-positive. Age, DM duration, chronic kidney disease stage ≥3, and dipeptidyl peptidase-4 inhibitor use, not using metformin, were associated with QFT-positivity. Preventive therapy (3HP: 138; 9H: 62) was administered in 200 (76.6%) QFT-positive patients. The completion rates of 3HP and 9H were 84.1% and 79.0%, respectively ( P = .494). Nine (6.5%) and zero patients in the 3HP and 9H groups, respectively, developed systemic drug reactions ( P = .059); 78.3% and 45.2% had ≥1 adverse drug reactions ( P < .001); and post-treatment QFT conversion rates were 32% and 20%, respectively ( P = .228). Conclusions: LTBI prevalence exceeds 25% in elderly patients with pDM. Under care from a collaborative multidisciplinary team, the completion rate of preventive therapy, regardless of regimen could approach, or even exceed 80% in this population. Abstract : The latent tuberculosis infection prevalence exceeds 25% in elderly patients with poorly controlled diabetes mellitus (DM), particularly those with a long DM duration. The completion rate of preventive therapy, regardless of the regimen, approaches 80% in this population under a collaborative framework.